The Impact of the COVID-19 Pandemic on the Resistance Level of Mycobacterium Tuberculosis in Suspected Tuberculosis Patients at the Surakarta Central General Hospital - Sutanto, Yusup Subagio; Sutanto, Magdalena; Harti, Agnes Sri (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Analysis of the impact of the Covid-19 pandemic on the resistance level of Mycobacterium tuberculosis (MTb) isolates to Anti Tuberculosis Drugs (ATD) needs to be carried out considering the level of MTB resistance is an important factor in the occurrence of Multidrug-Resistant TB (MDR-TB) in Indonesia. The purpose of the study was to analyze the impact of the Covid-19 pandemic on the level of resistance of MTb isolates of patients with suspected TB in Surakarta.Subjects and Method: This research is a quantitative descriptive study with a retrospective Cohort based on the medical record data of suspected TB patients at Surakarta Central General Hospital in 2020 – 2021. The sampling technique was random sampling with a total of 200 samples each year. Data analysis used the SPSS 21 program.Results: Characteristics of respondents with suspected TB patients who visited the Surakarta Central General Hospital in 2020 and 2021, mostly in men and occurring in productive ages 36-55 years. The most effective type of ATD against MTb isolates is Rifampicin with a mean rank of 6.00 and a p=0.035. While Ethambutol is ineffective as an ATD with a mean rank of 58.00 and a p<0.001. The results of the Wilcoxon test analysis showed there was a significant difference in the level of resistance or sensitivity of MTb isolates in 2020 and 2021 with a p-value=0.000.Conclusion: There is a significant effect of the impact of the Covid-19 pandemic on the level of resistance or sensitivity of MTb isolates of patients with suspected TB in the Surakarta area in 2020 and 2021.Keywords: pandemic, Covid-19, resistance, MTb isolates, ATDCorrespondence: Yusup Subagio Sutanto. Department of Pulmonology and Respiratory Medicine, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: yusupsubagiosutanto@gmail.com. Mobile: +62811284165.Indonesian Journal of Medicine (2022), 07(01): 28-38https://doi.org/10.26911/theijmed.2022.07.01.04